Report on Adjunct Professor Abdul Halim Ali visit to the Faculty of Social Sciences 25-30 September 2013. - Sharifah S., Wan Ahmad (Faculty of Social Sciences, 2013)
For the visit, there were two main objectives identified. The first objective was to continue on the agenda for capacity building among the young academics. The second objective was to provide academic training for students and staff through lecture, seminar and reading circles